What are Bogus Journal - Renandya, Willy A. (Widya Mandala Catholic University Surabaya, 2014)
Abstract The purpose of this paper is to warn novice researchers/writers of the danger of publishing in journals of questionable quality (often referred to as bogus, scam or predatory journals) and highlight key characteristics of these journals and their method of operation. Understanding the characteristics and how they operate could help us avoid publishing our work in scam journals. These journals claim (falsely) that they employ a blind review process by experts in the field, promise quick turnaround, claim legitimacy by quoting the ISSN and listing a number of databases in which they are indexed (e.g., EBSCO, DOAJ and PROQUEST). The paper outlines 15 reasons why as members of the academic community we should shun journals of dubious quality. The key message of this paper is that before we send our scholarly work to academic journals, we need to invest time doing our due diligence, making sure that our target journal is a legitimate and respectable outlet for our work.